Saberes científicos e pedagógicos de conteúdo expressos por professores de química em duas escolas públicas em Santo Antônio de Leverger - MT - Oliveira, Laura Paula de (2022)
This research seeks to understand the scientific and pedagogical knowledge of contents expressed by high school chemistry teachers from two state schools in the municipality of Santo Antônio de Leverger-MT. In this sense, the fundamental question of the research expressed as follows: how are the scientific and pedagogical knowledge of chemistry contents underlying the teaching of teachers, when reporting the teaching they perform in high school, are configured, and expressed? We take as the basis for the theoretical framework authors such as Tardif, Pimenta, Shulman and Gauthier et. al., because these deal with teaching knowledge. This research has as participants three teachers, two participants of the urban school State School Dr. Hermes Rodrigues de Alcântara (HERA) and one participant of the school of the field Faustino Dias de Amorim State School (FDA). The methodology of the qualitative approach is assumed based on the assumptions of Narrative Research as a research procedure, because it provides the researcher with a rigorous study of the teachers' experiences, their professional development, as well as the construction of their pedagogical knowledge, and how such knowledge is acquired. As for the investigative instruments, the following were used: questionnaires for the characterization of the subjects and semistructured interviews. To analyze the field texts, and from this construct the research texts, discursive textual analysis (ATD) was used, because it allows the emergence of new and significant readings of this teaching reality. Thus, we realize that the research subjects show mastery of scientific content, demonstrate sensitivity when seeking methodologies that facilitate the student's learning, bringing the specific contents closer to the reality of the same, thus expressing their experience in teaching, express a concern to work aligned not only to the BNCC, but also in addressing contents that are not specified in the BNCC, revealing a connection between their peers. They externalize the lack of better physical structures and the need for training offers by the State of Mato Grosso. In this way, we hope that this study will collaborate with the reflections and discussions in this scenario, with the purpose of understanding the convergence between scientific knowledge and pedagogical knowledge of chemistry content and thus contributing to the formation of future teachers.